Strategi Branding Berbasis Inovasi dan Kewirausahaan Sosial Untuk Penguatan Daya Saing dan Citra Produk Madu Kelulut - I Putu Gede Didik Widiarta; I Kadek Sudiarsana; Riki Andika; Faisal Azmi (Paser Institute Management and Busines, 2025)
Stingless bee honey (kelulut honey) industry in Indonesia holds substantial economic and ecological potential but continues to face challenges in branding and market competitiveness. This study aims to formulate a branding strategy based on innovation and social entrepreneurship to strengthen the competitiveness and image of stingless bee honey products in Samarinda, East Kalimantan. A descriptive–qualitative approach was employed, integrating Internal Factor Evaluation (IFE), External Factor Evaluation (EFE), Internal–External (IE), and SWOT analyses to assess internal capacities and external dynamics. The findings reveal that the primary strengths of kelulut honey enterprises lie in eco-friendly innovation, sustainable packaging, and community-based cooperative systems that enhance economic solidarity among beekeepers. The total IFE score of 3.12 and EFE score of 2.88 position the industry in the Growth and Build Strategy quadrant, indicating a favorable context for proactive development through innovation and strategic collaboration. Priority strategies include eco-branding initiatives, halal and organic certification, cooperative-based digital marketing training, and cross-sector partnerships involving government, academia, and tourism sectors. The study concludes that the integration of innovation, social entrepreneurship, and digital transformation forms a critical foundation for sustainable branding and the advancement of kelulut honey as a leading regional product in the context of green economy development.